2017
DOI: 10.1007/s11418-017-1165-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ultrasound-assisted enzymatic hydrolysis extraction of quinolizidine alkaloids from Sophora alopecuroides L. seeds

Abstract: Quinolizidine alkaloids are the main bioactive components in Sophora alopecuroides L. This study reports a novel ultrasound-assisted enzymatic hydrolysis method for the extraction of these important alkaloids. Box-Behnken design, a widely used response surface methodology, was used to investigate the effects of process variables on ultrasound bath-assisted enzymatic hydrolysis (UAEH) extraction. Four independent variables, pH, extraction temperature (°C), extraction time (min) and solvent-to-material ratio (mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Extraction time (min) 5 Thus, the use of UAE is useful to obtain an efficient extraction of alkaloids from A. muricata. RSM tools have been used to optimize the extraction of ALKs using UAE in tubers of the Stephania cambodica plant [20] and Sophora alopecuroides [21].…”
Section: Peel Seeds Columella Pulpmentioning
confidence: 99%
See 2 more Smart Citations
“…Extraction time (min) 5 Thus, the use of UAE is useful to obtain an efficient extraction of alkaloids from A. muricata. RSM tools have been used to optimize the extraction of ALKs using UAE in tubers of the Stephania cambodica plant [20] and Sophora alopecuroides [21].…”
Section: Peel Seeds Columella Pulpmentioning
confidence: 99%
“…Vinatoru et al [32] reported an increase in the percentage (77%) of alkaloid extraction from ipecacuana root (Cephaelis ipecacuanha) and Jaborandi leaf (Pilocarpus microphyllus) when the extracts were obtained using UAE compared to the extraction using Soxhlet (22%). Additionally, Wang et al [21] reported that alkaloid extraction from Sophora alopecuroides seeds produced the highest extraction yield (4.6% and 38.3%) when compared to extraction using reflux heating and enzymatic extraction, respectively.…”
Section: Peel Seeds Columella Pulpmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al for the analysis of cytisine and other quinolizidine alkaloids from Sophora alopecuroides L. seeds applied the hydrophilic interaction chromatography (HILIC) technique that uses a polar stationary phases such as silica or a polar bonded phases in conjuction with a mobile phase containing an appreciable quantity of water combined with a higher proportion of a less polar solvent (often acetonitrile). In the procedure, analytes were separated on an amide column with a mobile phase containing acetonitrile, water, formic acid, and ammonium acetate [22].…”
Section: Introductionmentioning
confidence: 99%
“…Matrine (MAT), an alkaloid derived from Sophora flavescens , possesses multiple pharmacological activities, including anti-cancer ( Cao and He, 2020 ), anti-inflammatory, and immunosuppressive ( Oveissi et al, 2019 ). Molecularly imprinted solid-phase and ultrasound-assisted enzymatic methods are used to extract MAT ( Guo et al, 2011 ; Wang H. et al, 2018 ), which has been used to treat Alzheimer’s disease, spinal cord injury, and rheumatoid arthritis ( Zhang H. et al, 2020 ). MAT is injected intraperitoneally at 10–250 mg/kg, and within this range, the injected drugs may have corresponding pharmacological effects ( Wang M. et al, 2019 ; Balkrishna et al, 2020 ; Sun N. et al, 2020 ).…”
Section: Nature Productsmentioning
confidence: 99%